2002
DOI: 10.1620/tjem.197.101
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteogenic Protein-1 Expression by Interleukin-1.BETA. in Cultured Rabbit Articular Chondrocytes.

Abstract: To elucidate the effects of interleukin-1beta (IL-1beta) on osteogenic protein-1 (OP-1) gene expression in a polylayer culture of rabbit articular chondrocytes, we measured rabbit OP-1 mRNA using quantitative TaqMan reverse transcriptase-polymerase chain reaction (RT-PCR) techniques. Rabbit articular chondrocytes were isolated and cultured in minimum essential medium eagle alpha modification containing 10% fetal bovine serum for 7 days. IL-1beta was then added and cultures were continued for 48 or 96 hours. OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…To avoid the effect of growth factors present in the serum and to identify responses induced solely by IL‐1β and OP‐1, we selected serum‐free cultures. Although IL‐1β up‐regulated expression of endogenous BMP‐2 and OP‐1 in human cartilage in this study and in previous studies (28, 29) and in rabbit cartilage (34), IL‐1β had no stimulatory effect on the gene expression of the BMP and OP‐1 receptors. In contrast, it caused a decrease in the number of ALK‐2 and ALK‐3 receptors on the chondrocyte surface, whereas ALK‐6 appeared to be a constitutively expressed kinase that is not affected by IL‐1β or degenerative processes (35).…”
Section: Discussioncontrasting
confidence: 61%
“…To avoid the effect of growth factors present in the serum and to identify responses induced solely by IL‐1β and OP‐1, we selected serum‐free cultures. Although IL‐1β up‐regulated expression of endogenous BMP‐2 and OP‐1 in human cartilage in this study and in previous studies (28, 29) and in rabbit cartilage (34), IL‐1β had no stimulatory effect on the gene expression of the BMP and OP‐1 receptors. In contrast, it caused a decrease in the number of ALK‐2 and ALK‐3 receptors on the chondrocyte surface, whereas ALK‐6 appeared to be a constitutively expressed kinase that is not affected by IL‐1β or degenerative processes (35).…”
Section: Discussioncontrasting
confidence: 61%
“… M1-like Mediator (3.2); Instructor (3.3). [ [85] , [86] , [87] ] IL-4 Cytokine belongs to interleukins. • Inhibiting osteoclast formation from macrophages; • Attenuating the inflammatory level elevated by the excessive infiltration of M1-like macrophages; • Overturning TNF-α-involved osteocyte apoptosis progression.…”
Section: The Pivotal Roles Of Macrophages In Bone Regenerationmentioning
confidence: 99%
“…Inhibition of IL-1beta signalling with IL-1 receptor antagonist suppresses tissue growth and bone formation in rabbit models [ 86 ]. Furthermore, two different groups reported that IL-1beta could even stimulate in vitro cultured cartilage explants to express osteogenic protein-1 (OP-1) – an osteogenic marker, revealing a strong osteotropic function of IL-1beta in tissue development [ 87 ].…”
Section: The Pivotal Roles Of Macrophages In Bone Regenerationmentioning
confidence: 99%
“…Aggrecan: forward: CCGCTGTGAGGTGATGCA, reverse: CGTGGAGATGGCCCGATA, probe: ACACAACACCTTTCACCACG (Entrez nucleotide accession number: L38480; gi: 1220470). Sequences for the GAPDH primer set have been previously described (Yoshida et al, 2002): forward: CAACGTGTCGGTCGTGGA, reverse: ACCACCTTCTTGATGTC GTCATAC, probe: TGACCTGCCGCCTGGAGAAAGCTGCTAA.…”
Section: Rna Isolation Cdna Synthesis and Qpcrmentioning
confidence: 99%